One Genome, Multiple Phenotypes: Would Rhodnius milesi Carcavallo, Rocha, Galvão & Jurberg, 2001 (Hemiptera, Triatominae) Be a Valid Species or a Phenotypic Polymorphism of R. neglectus Lent, 1954? † - Campos, Fabricio Ferreira [UNESP]; de Oliveira, Jader; Santos Santana, Jociel Klleyton [UNESP]; Ravazi, Amanda; dos Reis, Yago Visinho [UNESP]; Marson Marquioli, Laura [UNESP]; Galvão, Cleber; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Aristeu da Rosa, João [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (MDPI, 2024)
Species of the Rhodnius genus have a complex taxonomy because the events of phenotypic plasticity and cryptic speciation make it difficult to correctly classify these vectors. During the taxonomic history of the genus, five synonymization events occurred. Additionally, some authors suggest that R. milesi possibly represent only phenotypic polymorphisms of R. neglectus. Thus, we analyzed the specific status of R. milesi in relation to R. neglectus using phylogenetic studies with the mitochondrial gene cytochrome B and the study of reproductive barriers. The phylogenetic reconstruction grouped R. milesi together with R. neglectus from different localities, demonstrating that these taxa represent the same species based on the phylogenetic species concept. Experimental crosses demonstrate the absence of pre- and postzygotic barriers under laboratory conditions. Additionally, when the hatch rates of crosses are compared to intraspecific crosses, it can be noted that they are high and very similar. Finally, the mortality rate of the hybrids does not indicate hybrid inviability, the absence of chromosome pairing errors does not indicate hybrid sterility, and the proportion between male and female hybrids demonstrates that Haldane’s rule was not acting. Therefore, we perform the formal synonymization of R. milesi with R. neglectus.
Keywords: experimental crosses; phylogenetic systematics; synonymization; taxonomy; triatomines